To simplify to a single power of 3, we can multiply the exponents:
(3^6)^2 = 3^(6*2) = 3^12
simplify to a single power of 3:
left bracket, 3, to the power 6 , right bracket, squared
7 answers
Simplify to a single power of 3:
3, to the power 6 , dot, 3, to the power 5
3
6
⋅3
5
3, to the power 6 , dot, 3, to the power 5
3
6
⋅3
5
To simplify this expression, we can use the property of exponents that states that when multiplying two numbers with the same base, we add the exponents.
So, 3^6 * 3^5 = 3^(6+5) = 3^11
Therefore, the simplified expression is 3^11.
So, 3^6 * 3^5 = 3^(6+5) = 3^11
Therefore, the simplified expression is 3^11.
Simplify to a single power of 3:
start fraction, 3, to the power 6 , divided by, 3, to the power 4 , end fraction
3
4
3
6
start fraction, 3, to the power 6 , divided by, 3, to the power 4 , end fraction
3
4
3
6
To simplify this expression, we can use the property of exponents that states that when dividing two numbers with the same base, we subtract the exponents.
So, (3^6) / (3^4) = 3^(6-4) = 3^2
Therefore, the simplified expression is 3^2.
So, (3^6) / (3^4) = 3^(6-4) = 3^2
Therefore, the simplified expression is 3^2.
Simplify to a single power of 3:
3, times, 3, cubed
3×3
3
3, times, 3, cubed
3×3
3
To simplify this expression, we can use the property of exponents that states that when raising a number to a power and then multiplying it by the same number, we add the exponents.
So, 3 * 3^3 = 3^(1+3) = 3^4
Therefore, the simplified expression is 3^4.
So, 3 * 3^3 = 3^(1+3) = 3^4
Therefore, the simplified expression is 3^4.